Transgenic line for characterizing GABA-receptor expression to study the neural basis of olfaction in the yellow-fever mosquito - Rouyar, Angela; Patil, Anandrao A.; Leon-Noreña, Melissa; Li, Ming; Coutinho-Abreu, Iliano V.; Akbari, Omar S.; Riffell, Jeff A. (Frontiers in Physiology, 2024)
The mosquito Aedes aegypti is an important vector of diseases including dengue, Zika, chikungunya, and yellow fever. Olfaction is a critical modality for mosquitoes enabling them to locate hosts, sources of nectar, and sites for oviposition. GABA is an essential neurotransmitter in olfactory processing in the insect brain, including the primary olfactory center, the antennal lobe. Previous work with Ae. aegypti has suggested that antennal lobe inhibition via GABA may be involved in the processing of odors. However, little is known about GABA receptor expression in the mosquito brain, or how they may be involved in odor attraction. In this context, generating mutants that target the mosquito’s olfactory responses, and particularly the GABAergic system, is essential to achieve a better understanding of these diverse processes and olfactory coding in these disease vectors. Here we demonstrate the potential of a transgenic line using the QF2 transcription factor, GABA-B1QF2−ECFP, as a new neurogenetic tool to investigate the neural basis of olfaction in Ae. aegypti. Our results show that the gene insertion has a moderate impact on mosquito fitness. Moreover, the line presented here was crossed with a QUAS reporter line expressing the green fluorescent protein and used to determine the location of the metabotropic GABA-B1 receptor expression. We find high receptor expression in the antennal lobes, especially the cell bodies surrounding the antennal lobes. In the mushroom bodies, receptor expression was high in the Kenyon cells, but had low expression in the mushroom body lobes. Behavioral experiments testing the fruit odor attractants showed that the mutants lost their behavioral attraction. Together, these results show that the GABA-B1QF2−ECFP line provides a new tool to characterize GABAergic systems in the mosquito nervous system.